World trade in 2020: The show must go on! COVID-19 pandemic, trade wars and deadlock at the WTO: Rules-based trade is under pressure and the EU must take the lead - Aljoscha Nau (Institut der deutschen Wirtschaft (IW), 2020)
Rules-based trade is under attack and the WTO is at risk of marginalization. The COVID-19 pan-demic and its detrimental effects on public health, global supply- and value chains and industrial production, have brought back national export restrictions and stopped the free flow of goods and people. Buzz words such as 'decoupling', 'sovereignty' and 'autarky' quickly returned to the global stage. Meanwhile the World Trade Organization (WTO) is facing an existential crisis due to a deadlock in negotiations, blockage of institutional reforms and paralysis of the dispute set-tlement mechanism (DSM). However, this policy paper argues that there might be hope, with countries experiencing the effects of disrupted trade and understanding: The show must go on! We are at crossroads: The global COVID-19 pandemic could either lead to more state interfer-ence, decoupling and a marginalization of global trade action or it calls for an unprecedented level of multilateral cooperation. This analysis claims that trade can serve as a powerful, low-cost, and immediate crisis response by securing the free flow of medical goods and personal protective equipment (PPE), lowering tariffs, and coordinating logistics. Second, trade will be essential for a speedy recovery of the global economy. Geographical diversification of supply- and value chains must not mean decoupling, and genuine COVID-19 measures to protect public health and security should not become a fig-leaf for protectionist policies. However, there is no alternative to WTO reform, given that the economic balance in the world has changed - while the WTO has not. Besides institutional reforms, the WTO and its members now have the chance to update its rulebook and to advance future trade policy on services, digital trade/e-commerce, and sustainability, as well as to restore a functional enforcement and dispute settlement mechanism. The EU can act as an 'honest broker' between the USA and China. Establishing an interim appeal arbitration mechanism in early 2020, the EU and Canada have taken the first steps. Onwards, the EU should take the lead to form a like-minded coalition of progress and to become a global standard-setter of its own. Now more than ever, the WTO needs to adapt to internal- and external shocks: The show must go on!
Keywords: F13; F02; H12; 330